THE INFLUENCE OF DIGITAL LITERACY PROBLEM BASED LEARNING MODELS ON STUDENT LEARNING OUTCOMES - sirait, gloria; Pasaribu, Sunggul; Purba, Melfa Uli Magdalena (Jurnal Ilmu Pendidikan Indonesia, 2024)
Higher education in the digital age demands the integration of digital literacy in a learning approach to prepare students to face the complexity of job market demands. In this context, Problem Based Learning (PBL) models offer a potentially effective approach in promoting deep understanding and critical thinking skills. Problem Based Learning (PBL) model, the focus of learning is on the chosen problem so that students not only learn concepts related to the problem that is the center of attention but also scientific methods to solve the problem. The research was carried out at HKBP Nommensen University located on Jl. Sangnawaluh No.4, Siopat Suhu, East Siantar District, Pematangsiantar City, North Sumatra, Zip Code 21136. The research period starts in January 2024 – July 2024 at the Biology Education Study Program at HKBP Nommensen Pematangsiantar University. The study population is all students of the Biology Education study program at HKBP Nommensen Pematangsiantar University. The type of research used in this study is a type of quasi-experimental research, which is research intended to determine whether or not there is an influence of the treatment given to students as research subjects. In this study, researchers used a pretest-postest control group design which aims to determine the learning outcomes of students before and after being treated. Based on the results of data analysis and hypothesis testing, there is a significant influence by using the Digital Literacy-based Problem Based Learning Model on Student Learning Outcomes and the Digital Literacy-based Problem Based Learning Model can be developed into an alternative learning model in lectures